Retextualização no gênero entrevista : processo de ressignificação da oralidade à escrita por discentes do 9º ano do ensino fundamental - Sousa, Carla Magda da Cunha (2018)
This Final Conclusion Paper is written in the format of a dissertation and investigates the process of retextualizing interviews about the theme of pregnancy in adolescence as a proposal for didactic intervention for teaching Portuguese Language. The subjects selected for this research were 36 students from a 9th grade elementary school from a state school in Itabaiana-SE. We believe that the discursive genre interview - in the oral and written modalities of the language - can promote sociocognitive challenges in the interactional process in textual production activities. To do so, we used as a research methodology the case study, analyzing a proposal of a sequence of activities developed in the classroom with the following steps: reading and characterization of the interview genre; proposing the publication of an interview with the subject of teenage pregnancy; preparation of a questionnaire for interviewing, interviewing with a health professional; and, finally, carrying out transcription and retextualization of the oral interview for writing with a publication on a social network page Facebook, from school. For the scope of our work, the works of Marcuschi (2010), Bakhtin (2011), Bronckart (2003), Schneuwly and Dolz (2004), Medina (1990), Fávero (1998,2000) and others . Data analysis revealed that the process of transferring the oral text to writing in retextualization activities, with the interview genre, can contribute to the improvement of the interpretative understanding and the written textual production of elementary school students.